Acupuncture Treatment for Nocturnal Crying in Pediatric Patients: A Systematic Review of Clinical Studies - Ang, Lin; Song, Eunhye; Lee, Hye Won; Kim, Jung Tae; Kim, Eunseop; Lee, Myeong Soo (Frontiers in Pediatrics, 2021)
Background: Nocturnal crying is a common condition in which children intermittently or continuously cry and fuss during the night, at certain times, or throughout the night. It is a common pediatric sleep disturbance for which medical assistance is highly sought by parents, and an alternative treatments for nocturnal crying is pediatric acupuncture. This review aimed to review the literature about the effectiveness and safety of pediatric acupuncture for nocturnal crying. Methods: Literature searches were performed on PubMed, the Cochrane Controlled Register of Trials (CENTRAL), Allied and Complementary Medicine Database (AMED), Chinese National Knowledge Infrastructure Database (CNKI), Wanfang Database, and Chinese Science and Technique Journals Database (VIP), OASIS, the Research Information Service System (RISS), and National Digital Science Library (NDSL) from the available date of inception until December 28, 2020. Two review authors independently screened the titles and abstracts of all relevant articles from the search to select eligible articles. All variants of clinical studies on acupuncture treatment for nocturnal crying, including case reports and case studies, were eligible. Data were independently extracted by two review authors using a standard data extraction form. Retrieved data are presented in a tabular form and narratively discussed. Results: We included 12 studies (10 case series and 2 case reports) with a total sample size of 2324 children recruited from the hospital outpatient department. All of the included studies were conducted in mainland China and administered acupuncture as the sole intervention. For the primary outcome, the total efficacy rate of acupuncture treatment for nocturnal crying was reported as 100% in 9 studies, 95% in one study, 94% in another study, and 86% in the remaining study. For the secondary outcome, one study reported a 14% recurrence rate, whereas another study reported an 11% recurrence rate after treatment. There were no follow-ups in most of the studies. None of the studies reported possible adverse events. Most children recovered after one treatment. Generally, the acupoints that were most frequently selected were acupoints EM30 and PC9. Conclusions: This comprehensive review suggested that pediatric acupuncture may be an effective treatment for nocturnal crying, which could be worth investigating further.